The Name of Metacommentary: Fredric Jameson. - Cole, Andrew (PMLA: Publications of the Modern Language Association of America, 2024)
In this article, the author discusses about American cultural critic Fredric Jameson and his comparative analysis of competing interpretive methods, Topics discussed include Jameson's massive contributions to scholarship, his notion of metacommentary, and use of the word metacommentary in the books "The Political Unconscious" and "Marxism and Form." Also mentioned are topics such as transcoding, cognitive mapping, and the political unconscious approaches used by Jameson for literary criticism.